Lipid profile of people with Diabetes mellitus type 2 and periodontal disease - Nassar, Patricia Oehlmeyer; Walker, Carolina Schmitt; Salvador, Camila Saturnino; Felipetti, Francielly Andressa; Orrico, Silvana Regina Perez [UNESP]; Nassar, Carlos Augusto (Elsevier B.V., 2012)
The objective of this study was to evaluate improvement of lipids and periodontal disease in patients with type 2 Diabetes mellitus, by means of the relationship between blood levels of total cholesterol and its fractions, triglycerides and clinical periodontal parameters. Twenty patients, in age-range 18-70 years, were selected and divided into 2 groups: (1) conventional periodontal scaling and root planing + controlled mechanic; (2) conventional periodontal scaling and root planing + controlled mechanical + maintenance therapy. The analyses were performed on day 0, 180 and 720 days, including plaque index, gingival index, probing depth and clinical attachment level, and evaluation of total cholesterol and its fractions, and triglycerides. The 2 groups presented significant reduction in clinical periodontal parameters, however, probing depth did not diminish significantly only in Group 1. There was significant improvement in all blood parameters in both groups. It was concluded that after 720 days of the experiment, there were significant improvements in clinical and blood parameters, in general. The group that received maintenance therapy also showed a more expressive improvement in clinical periodontal parameters, in general, suggesting that this therapy is important and necessary in patients with type 2 Diabetes mellitus and periodontal disease. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Lipid control; Diabetes mellitus; Periodontal disease; Maintenance therapy